Crash - Haggis, Paul; 1972-; 1968- (Santa Monica, CA : Lions Gate Entertainment, 2004)
A car accident brings together a group of strangers in Losb Angeles. Crash takes a provocative, unflinching look at the complexities of racial tolerance in contemporary America
Originally released as a motion picture in 2004
Special features: Director commentary; "The making of 'Crash' featurette"; deleted scenes; trailers
Director of photography, J. Michael Muro ; editor, Hughes Winborne ; music, Mark Isham ; costume designer, Linda Bass ; production designer, Laurence Bennett
Sandra Bullock, Don Cheadle, Matt Dillon, Jennifer Esposito, William Fichtner, Brendan Fraser, Terrence Howard, Chris "Ludacris" Bridges, Thandie Newton, Ryan Phillippe, Larenz Tate
MPAA rating: R; for language, sexual content and some violence
DVD, region 1; 5.1 and 2.0 Dolby Digital
Keywords: Racism; Traffic accidents; Feature films; Films for the hearing impaired; Drama -- Los Angeles -- California -- Racism; Drama -- Los Angeles -- California -- Traffic accidents; Feature films